1995
DOI: 10.1007/bf00212510
|View full text |Cite
|
Sign up to set email alerts
|

The decline of mink in Georgia, North Carolina, and South Carolina: The role of contaminants

Abstract: Since the 1960s, mink (Mustela vision) populations in Georgia, North Carolina, and South Carolina have declined, especially in the coastal plain. A prior study suggested that the decline may stem from environmental contaminants. Based on water quality data from each state, we identified 17 substances potentially related to the decline: aldrin, dieldrin, endrin, DDD, DDE, DDT, PCBs, chlordane, alpha-BHC, toxaphene, dibenzofuran, copper, chromium, cadmium, lead, arsenic, and mercury. Mink livers were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…NEHCs for both mink and bald eagle were exceeded at Sites 23,24,67,76,111,320,324,327,and 330. Elevated PCB concentrations have been previously documented in water and biota near Site 327 (USFWS 1996;Schmitt et al 1999;Zappia 2002), and PCBs were identified as a potential cause of reproductive dysfunction in mink from the coastal plain of Georgia, South Carolina, and North Carolina (Osowski et al 1995). We are not aware of contaminant studies evaluating the risk of total PCBs to piscivorous wildlife in the Mississippi River Basin downstream from Memphis (Site 76) or the Ohio River Valley (Sites 23, 24, and 67).…”
Section: Dieldrin -Mink Dieldrin -Bald Eaglementioning
confidence: 90%
See 2 more Smart Citations
“…NEHCs for both mink and bald eagle were exceeded at Sites 23,24,67,76,111,320,324,327,and 330. Elevated PCB concentrations have been previously documented in water and biota near Site 327 (USFWS 1996;Schmitt et al 1999;Zappia 2002), and PCBs were identified as a potential cause of reproductive dysfunction in mink from the coastal plain of Georgia, South Carolina, and North Carolina (Osowski et al 1995). We are not aware of contaminant studies evaluating the risk of total PCBs to piscivorous wildlife in the Mississippi River Basin downstream from Memphis (Site 76) or the Ohio River Valley (Sites 23, 24, and 67).…”
Section: Dieldrin -Mink Dieldrin -Bald Eaglementioning
confidence: 90%
“…Other studies also have reported that mercury concentrations in these regions represent a risk to avian and mammalian wildlife (Halbrook et al 1994;Osowski et al 1995;Ambrose et al 2000;Adair et al 2003). Mercury has been suspected to cause reproductive effects, organ toxicity, and mortality in prothonotary warbler (Protonotaria citrea), mink, and river otter throughout the southeastern United States (Halbrook et al 1994;Osowski et al 1995;Adair et al 2003). Ambrose et al (2000) reported that mercury concentrations in peregrine falcon (Falco peregrinus anatum) breeding in the Yukon River Basin were associated with lower nest success.…”
Section: Dieldrin -Mink Dieldrin -Bald Eaglementioning
confidence: 98%
See 1 more Smart Citation
“…Dieldrin levels were highest among mammals in the coastal areas of North and South Carolina. This could contribute to the decline of the mink population (75). A study conducted from 1991 to 1995 of mink in Canada also tracked longrange atmospheric transport of dieldrin and reported concentration levels that may affect future population levels (76).…”
Section: Nasqan Hbnmentioning
confidence: 99%
“…Organochlorine pesticides have varying effects on endocrine functions, fertility and the immune system of birds and mammals [13]. Some work have confirmed the decrease in reproduction, growth and increased risk of hyperthyroidism in mammals by pesticides [14] [15]. Many experiments corroborate the decline in fertility, increased risk of mis-carriage, premature deliveries, birth defects, cancer, damage to DNA and accumulation of pesticides in human's milk [16]- [19].…”
Section: Resultsmentioning
confidence: 99%